Implementing Process Writing Strategy Using Weblogs to Improve Students’ Ability in Writing Descriptive Text - Syarofi, Abdullah; Kuswahono, Deny; Rizky, Hendi (Lingua Cultura, 2018)
This research aimed at improving the ability of the X MIA 3 students of Senior High School 2 Lamongan in writing descriptive text through the implementation of process writing strategy facilitated by weblogs. This research was a collaborative action research which consisted of four stages: planning, implementing, observing, and reflecting. The data required were gathered by using observation checklists, field notes, and questionnaire. The results of the above-mentioned instruments indicate that the students show their active participation and good interest in attending the learning activity. The group discussion regarding the assigned objects in the pre-writing stage and the implementation of media weblogs can make the students participate more actively when the learning procedure is implemented. Meanwhile, the writing ability of the students also improves as proven by the fact that every student can successfully increase his/her score in at least 10 points, which indicates an improvement to a higher level. It is also found that all of the writing aspects, such as content, organization, and language are improved due to the activity of pre-writing that the students do. The observation towards the assigned objects and idea generation makes the students have a clear plan regarding what to write on the draft.Â